(untitled) - Hooks, William H.; Duke, Kate (Gareth Stevens Publishing, 1997)
Five-year-old Eli's enthusiasm for saving the planet gets out of hand as he continues to fill his room with more and more junk he intends to recycle.
K-3
Keywords: Environmental protection; Fiction; Recycling (Waste, etc.); Fiction